Pengembangan PENGEMBANGAN E-MODUL MENGENAL LINGKUNGAN DENGAN TARI KELAS IV SD - Safitri Angga Dewi; Deasylina da Ary (Postgraduate, University of Mataram, 2024)
Dance learning in elementary schools is no less essential in learning activities. However, teachers still need to clarify many things regarding the purpose of learning dance in schools, where teachers still think that learning dance must teach students to become dancers. Therefore, this study aims to develop e-modules on recognizing the environment with dance for grade IV elementary school students. This type of research is development research with the ADDIE development model. The data collection techniques used in the study were observation, interviews, documentation, questionnaires, and tests. The data analysis techniques used are normality test, t-test, and N-Gain test. The results of the feasibility assessment of e-modules to recognize the environment with dance from material experts obtained a score of 92.26%. In comparison, the evaluation of media experts obtained a value of 89.02%. In addition, responses from users on product trials obtained a percentage of 98.18% from students and 100% from class teachers. The effectiveness of e-modules to recognize the environment with dance is evidenced in the t-test which obtained a significance value of 0.001 less than the significance level of 0.05, which means that there is a significant effect of using e-modules to recognize the environment with dance. In the N-Gain test, the result is 82.80, which can be concluded that the e-module of recognizing the environment with dance that has been developed is declared feasible and effective in learning dance.